2010
DOI: 10.1182/blood-2009-11-252270
|View full text |Cite
|
Sign up to set email alerts
|

An exquisite cross-control mechanism among endothelial cell fate regulators directs the plasticity and heterogeneity of lymphatic endothelial cells

Abstract: Arteriovenous-lymphatic endothelial cell fates are specified by the master regulators, namely, Notch, COUP-TFII, and Prox1. Whereas Notch is expressed in the arteries and COUP-TFII in the veins, the lymphatics express all 3 cell fate regulators. Previous studies show that lymphatic endothelial cell (LEC) fate is highly plastic and reversible, raising a new concept that all 3 endothelial cell fates may coreside in LECs and a subtle alteration can result in a reprogramming of LEC fate. We provide a molecular bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
111
1
1

Year Published

2010
2010
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(120 citation statements)
references
References 52 publications
7
111
1
1
Order By: Relevance
“…6,7 COUP-TFII and Prox-1 are essential for the maintenance of the identity of the lymphatic endothelial cells following their differentiation. 8 The primary lymphatic networks then enlarge by sprouting lymphangiogenesis induced by the VEGFR-3 ligand VEGF-C. By upregulation of VEGFR-3 expression independently of Prox-1, T-box transcription factor 1 supports the growth and maintenance of the gastrointestinal lymphatic vessel network. 9 Lymphatic vessel subtypes are specialized and patterned by a remodeling program.…”
Section: Lymphatic Vessel Developmentmentioning
confidence: 99%
“…6,7 COUP-TFII and Prox-1 are essential for the maintenance of the identity of the lymphatic endothelial cells following their differentiation. 8 The primary lymphatic networks then enlarge by sprouting lymphangiogenesis induced by the VEGFR-3 ligand VEGF-C. By upregulation of VEGFR-3 expression independently of Prox-1, T-box transcription factor 1 supports the growth and maintenance of the gastrointestinal lymphatic vessel network. 9 Lymphatic vessel subtypes are specialized and patterned by a remodeling program.…”
Section: Lymphatic Vessel Developmentmentioning
confidence: 99%
“…Notch, which is selectively expressed in arterial endothelial cells and acts as a downstream effector of VEGF-induced arterialization signal (Lawson et al 2001Weinstein and Lawson 2002;Lanner et al 2007;Siekmann and Lawson 2007), represses the expression of COUP-TFII, Prox1, and podoplanin through Hey1 . COUP-TFII, a nuclear receptor that is selectively expressed in the venous compartment, has been shown to interact physically and functionally with Prox1 in LECs to direct a developmental program that specifies LEC fate Yamazaki et al 2009;Kang et al 2010;Srinivasan et al 2010). Interestingly, Prox1 and COUP-TFII concertedly suppress VEGF signaling by downregulating the expression of the major VEGF receptors VEGFR-2 and NRP-1 .…”
Section: Plasticity Of Lymphatic Endothelial Cell Fate-lymphatic Equimentioning
confidence: 99%
“…In fact, it has been proposed that the three endothelial cell fate regulators-namely, Notch (arterial) (Shawber et al 2007), COUP-TFII (venous) (You et al 2005), and Prox1 (lymphatic) -are all expressed in LECs and cross-regulate one another Kang et al 2010). Notch, which is selectively expressed in arterial endothelial cells and acts as a downstream effector of VEGF-induced arterialization signal (Lawson et al 2001Weinstein and Lawson 2002;Lanner et al 2007;Siekmann and Lawson 2007), represses the expression of COUP-TFII, Prox1, and podoplanin through Hey1 .…”
Section: Plasticity Of Lymphatic Endothelial Cell Fate-lymphatic Equimentioning
confidence: 99%
“…Studies have revealed a role for Notch signalling upstream of PROX1 during mammalian lymphangiogenesis in vitro and in neolymphangiogenesis in the adult but the role of this pathway in the context of embryonic induction of LEC fate remains unclear (Kang et al, 2010;Niessen et al, 2011;Zheng et al, 2011). In zebrafish, in the absence of Delta-like ligand 4 (Dll4), the cells that leave the vein during secondary sprouting all acquire BEC identity and give rise solely to vISVs .…”
Section: Reviewmentioning
confidence: 99%